PENERAPAN METODE K-MODES UNTUK PROSES PENENTUAN PENERIMA BANTUAN LANGSUNG TUNAI (BLT) - Putri Kartikasari, Yolanda Aprilia; Agus Pranoto, Yosep; Rudhistiar, Deddy (JATI (Jurnal Mahasiswa Teknik Informatika), 2021)
The data collection of potential recipients of Jatikerto Village BLT has been carried out using technology, namely Microsoft Excel. There are several criteria that must be considered so that the distribution of BLT funds is right on target. In the process of determining BLT recipients, problems often occurred. This obstacle was due to the large number of data on potential BLT recipients and the difficulty in processing the data because it took a long time and was more likely to produce errors when determining BLT recipients.The system created applies the K-Modes Clustering method for the determination of BLT recipients. So that it can help make it easier for officers in determining BLT recipients and can shorten the time in data processing. This system is designed based on a website with phpMyAdmin as the database to make it easier for the admin or village party to access the system anywhere.Based on the results of the system testing that has been carried out, the system for determining BLT recipients is quite good in clustering BLT recipient data against the k-modes clustering algorithm using the old BLT data in Jatikerto village and the value is 96.875%. From the results of the system error test, the error value is 0%. From the results of the admin user test, it was found that 25% strongly agreed and 75% agreed, while from the results of the citizen user testing, the value was 8.3% strongly agreed, 87.5% agreed and 4.2% disagreed.